A cross sectional study on quitting behavior of tobacco use among rural population in Dehradun, Uttarakhand - Imtiaz, Danish; Kandpal, Sunil Dutt; Juyal, Ruchi (Indian Journal of Community Health, 2015)
Background: Nearly 275 million adults use tobacco in India, which contributes substantially to potentially preventable morbidity and mortality. Awareness towards tobacco is increasing steadily but its role towards cessation is questionable. There is little evidence available about quitting behavior in the Uttarakhand region. Aims & Objectives: To assess the quitting behavior among current tobacco users in a rural population of Dehradun. Material and Methods: The study was cross sectional in nature carried out among 993 current tobacco users aged 10 years and above in the field practice area and quitting behavior was assessed using a pretested and predesigned questionnaire. Result: Of the 993 Current tobacco users, 38% and 40% of the current smokers and current smokeless tobacco users respectively had attempted to quit smoking and smokeless tobacco use in the past 12 months. 54.3% of the smokers wanted to quit smoking with majority of male smokers (56.3%) willing to quit smoking compared to only 40.5% of female smokers. 36.0% of the smokeless tobacco users wanted to quit smokeless tobacco use where in contrast more female smokeless tobacco users (39.3%) wanted to quit smokeless tobacco compared to 33.3% of males. Conclusion: Previous quit attempts were found to be more among males compared to females. The desire to quit smoking tobacco was also found to be more among males as compared to female smokers. More females showed desire to quit smokeless tobacco compared to males.